2019
DOI: 10.3390/sym11081037
|View full text |Cite
|
Sign up to set email alerts
|

Necessary and Sufficient Optimality Conditions for Vector Equilibrium Problems on Hadamard Manifolds

Abstract: The aim of this paper is to show the existence and attainability of Karush–Kuhn–Tucker optimality conditions for weakly efficient Pareto points for vector equilibrium problems with the addition of constraints in the novel context of Hadamard manifolds, as opposed to the classical examples of Banach, normed or Hausdorff spaces. More specifically, classical necessary and sufficient conditions for weakly efficient Pareto points to the constrained vector optimization problem are presented. The results described in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Once introduced the concept of invexity, we can know discuss the existence of critical points. For this purpose, we will adopt the definition given by Ruiz-Garzón et al [13]: This result is a generalization to Riemannian manifolds of similar result to the one achieved by Craven and Glover [16].…”
Section: Unconstrained Casementioning
confidence: 99%
See 1 more Smart Citation
“…Once introduced the concept of invexity, we can know discuss the existence of critical points. For this purpose, we will adopt the definition given by Ruiz-Garzón et al [13]: This result is a generalization to Riemannian manifolds of similar result to the one achieved by Craven and Glover [16].…”
Section: Unconstrained Casementioning
confidence: 99%
“…In Ruiz-Garzón et al [13] we obtained first-order optimality conditions for the scalar and vector optimization problem on Riemannian manifolds, but not second order conditions, it will be discussed in this article. Also, in Ruiz-Garzón et al [14] we prove the existence of optimality conditions from KKT to constrained vector optimization problems on Hadamard manifolds as a particular case of equilibrium vector problems with constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Two years later, Ruiz-Garzón et al [26] extended these properties on Riemannian manifolds in the smooth case. In 2019, Ruiz-Garzón et al [27] showed the existence of KKT optimality conditions for weakly efficient Pareto solutions for vector equilibrium problems, with particular focus on the Nash equilibrium problem, but only in the differential case.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, in 2019, in Ruiz-Garzón et al [25], we studied the constrained vector optimization problem as a particular case of the equilibrium vector with constraints problem on Hadamard manifolds.…”
Section: Introductionmentioning
confidence: 99%